Improved Reduction on Amines of Dihydrophenophosphazine System - Cui1, Jin-Hai; Zhang1, Shu-Fen; Zhang2, Lei; Yin3, Zhi-Gang (Asian Journal of Chemistry, 2014)
With the addition of 15-20 % more of water in absolute methanol dissolvent, the hydrogenation reduction on four of nitro-derivatives of 5,10-dihydro-phenophosphazine system was improved from 75 to 95 %, yet with reduced time and more efficiency. Both the adsorption and desorption of nitro-derivative on the surface of Pd/C and the concentrate of methanol aqueous solution were proved to be the dominating factors for the reaction rate of hydrogenation reduction, the optimistic concentrate of methanol aqueous solution were fitted by nonlinear Gaussian function and be verified by experiments also.